Benefits and limitations of the transparent orthodontic appliance: a narrative review - Coelho, Beatriz Santos (2021)
Transparent orthodontic appliances are similar to a bruxism plate, made with materials that allow a better aesthetics to the patient throughout the treatment. With the increased search of patients for this type of appliance, this study seeks to describe how the knowledge on the benefits and limitations of transparent orthodontic appliances influence and contribute to the treatment. This is a qualitative, explanatory and deductive study based on a narrative review of the literature on the benefits and limitations of the transparent orthodontic appliance. The following descriptors and their combinations were used: ‘transparent orthodontic aligners’ and ‘invisalign’ in the SCIELO and Google Scholar databases. A total of 35 articles related to the topic were found, among these articles, 8 were selected. There are several benefits to aligner systems, including aesthetics, comfort, reduced chair time and the fact that they can be removed for meals and oral hygiene procedures. Despite the evolution, the degree of treatment difficulty in cases of some malocclusions limits or prevents the use of aligners, as there may be a need for combinations with conventional orthodontic appliances. The results of the research on the worked topic are of fundamental importance in the professional's daily clinical routine, as this way, he/she will have knowledge of when to use the aligner in question properly.